Effects of Game-Based Training Approach on Physical Abilities in Male Youth Volleyball Players - Dagnachew Kebede; Alemayehu Belay; Alemayehu Wubale (Pamukkale University, 2023)
The study aimed to determine the effects of a game-based training approach on the physical abilities of male youth volleyball players. A two-way mixed design was used. Forty young male volleyball players (age: 15.49±1.36 years old; height: 175.50±0.02 cm; weight: 65.50±1.32 kg; experience: 3.39±1.27 years old) participated in this study. Participants were randomly assigned into two equal study groups, a Traditional Training Group (TTG; n = 20) and a Game-based Training Group (GTG; n = 20). TTG uses a traditional training program in which coaches coach athletes, give individual feedback, and perform technique-focused workouts. GTG follows a 12-week simple volleyball game-based training program. Before and after 12 weeks of training, both groups measured their agility, endurance, power, and speed. A two-way mixed design (2 × 2) ANOVA was used to compare the differences between subjects and repeated measure variables. All coefficients are considered significant at p ≤ .05. As a result, significant differences were found within-subject and between groups in male youth volleyball players' physical abilities. In conclusion, the 12-week game-based training approach effectively improved the physical performances of male youth volleyball players. To support this notion, an additional study is necessary.